PREVALENCIA DE Neospora caninum EN BOVINOS DE UNA EMPRESA GANADERA DE LA SIERRA CENTRAL DEL PERÚ - Puray Ch., Nidia (2012)
Neosporosis has become a parasitosis of economic importance for dairy cattle due to abortions and neonatal mortality. The study was conducted in 2003 to determine the prevalence of Neospora caninum in cattle of the SAIS Pachacutec farm, located in the highlands of Peru. In total, 347 sera sampleswere collected fromBrown Swiss adult cows. Samples were evaluated through the indirect fluorescent antibody test (IFAT). Results indicated that 12.4 ± 3.5%(45/347) of the animals presented antibodies against N. caninum (corrected prevalence: 13.2 ± 3.5%). Theminimumandmaximumseroprevalence was 2.5 and 19.6% in the 7 sampled herds, without statistical differences. All herds had at least one positive animal. The results confirmed the existence of a moderate prevalence of N. caninum in the studied area.